Islamic Legal Perspectives on the Ethical Issues of Modern Biotechnology: A Case Study of Human Cloning and Genetic Engineering in Nigeria - Salusi Salusi; Seyyed Javed Hosseini (Samarinda International Journal of Islamic Studies (SIJIS), 2025)
Modern biotechnology, specifically human cloning and genetic engineering, presents a significant ethical dilemma in Nigeria, where Islamic law deeply influences social and legal conduct. This research addresses the tension between rapid scientific advancement and the preservation of Islamic moral values, focusing on the absence of a harmonized bioethical framework in Nigeria’s pluralistic legal system. The primary objective is to evaluate the permissibility and ethical boundaries of these technologies using the Maqasid al-Shari’ah (Objectives of Sharia) framework. Employing a Systematic Literature Review (SLR) based on the PRISMA protocol, this study synthesizes 25 reputable sources (2021–2026) covering Sharia jurisprudence and Nigerian healthcare policy. The findings reveal a sharp legal distinction: reproductive cloning is strictly prohibited (Haram) due to its disruption of genealogical integrity (Nasab), whereas somatic gene therapy for restorative purposes—particularly for Nigeria's sickle cell crisis—is highly encouraged as a form of medical necessity (Dharurah). The study concludes that the "ethical conflict" in Nigeria is not a theological rejection of science but a governance issue. It proposes a "Bio-Sharia" regulatory model that integrates Islamic ethical filters with national health legislation. This approach ensures that Nigeria can adopt life-saving genomic innovations without compromising the religious and cultural sanctity of its Muslim populace, ultimately providing a blueprint for other Muslim-majority nations in the Global South.